Peran krusial manajemen dalam mengoptimalkan pelayanan perpustakaan: suatu tinjauan literatur - Mubarok, Ramdanil (Nur Science Institute, 2024)
The library is a vital information center for educational institutions and the general public. In today's information age, the role of management in optimizing library services is becoming increasingly important. This literature review aims to identify and analyze the crucial role of management in an effort to optimize library services. This research uses a library research approach. The results show that library management plays a crucial role in coordinating the human, financial, technological, and collection resources of the library to meet the needs of its users. This requires effective management strategies in resource management, service planning and development, performance evaluation, and adaptation to environmental change. In addition, other findings indicate that there are challenges facing library management, including financial constraints, technological change, the need for a skilled workforce, and demands for service innovation. In conclusion, library management has a crucial role to play in optimizing library services. With a good understanding of the principles of effective management, libraries can become more responsive to the needs of users and play an active role in supporting the achievement of educational and community development goals through the provision of access to quality information.